Profesionalisme Guru dalam Pengembangan Mutu Pendidikan di Era Milenial - Abnisa, Almaydza Pratama (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to discuss teacher professionalism in developing the quality of education in the millennial era. This research is a field research study, in which the preparation of data is carried out in the field to make observations of phenomena in a natural state. Data collection techniques use field observation, interview, and documentation methods. The data analysis method is to use stages starting from data refining, data reduction, data presentation, and conclusion. Test the validity of data through credibility tests, transferability tests, dependability tests, and comformability tests. The results of the data analysis show that teacher professionalism is an effort made to improve the level or degree of a teacher's profession concerning teacher abilities, both mastery of teaching material or mastery of teaching methodology, as well as teacher professional attitudes regarding teacher motivation and commitment in carrying out duties as teachers. Teachers must develop their profession in accordance with the quality of education in this millennial era which provides flexibility for teachers to be able to freely choose, create, use, and develop their learning